Chapter Beach sediment dynamics from natural radionuclides point of view - Miquel Armengol, Neus (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This work assesses the use of natural radionuclides as tracers of marine sediment dynamic in a heterogeneous beach in Spain. Multivariant statistics was used to evaluate the spatial variability of the activity concentration of natural radionuclides. The statistics applied for the temporal variability showed that some erosion agents influence the activity concentration found for various natural radionuclides during erosion and accumulation periods. The results of the different analysis suggested that the radionuclides studied could be used as tracers of marine sediment dynamic in beaches.